Open Access and Institutional Repositories in Bulgaria - Simeonov, Georgi; Stanchev, Peter (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2011)
The paper presents the current situation regarding open access, institutional repositories (IRs) and journals in Bulgaria. It focuses on epublications and related research content available in digital format on the web. It includes development of IRs in Bulgaria and discusses their content, software and various access restrictions that apply to content. A survey is used to identify current state of open access for IR and e-journals not just those that are using OAI-PMH.